Killer kettleball training WOD bible : 200+ cross training KB workouts - Selter, P., ....- ([s.l.] : Shredded Society, 2014)
BONUS – exclusive content upon redemption. Kettlebells… the Russian super weapon that has been dominating the fitness industry for the past decade! Here is A Preview Of What the Killer Kettlebell WOD Bible contains: A comprehensive list of the health benefits of Cross Training In depth terminology to help you understand the abbreviations and lingo used in Cross Training An explanation of what a kettle actually is along with its Russian heritage Benefits of kettlebell training revealed ***must read!*** Common kettlebell exercises form explained – including photos Kettlebell training mistakes revealed, along with how to avoid them 200+ Cross Training kettlebell workouts! 20 assorted bonus WODs And Much More!
Keywords: Krachttraining